Transformation of number head together method as adaptive way from COVID-19 effects - Wulandari, Rossy; Dayana, Yuliana Fatima (CV. Mitra Palupi, 2021)
Background: Â COVID-19 affects education systems and leading to the closure of schools, universities and colleges. As the consequence, the learning process is done from home in which needs some adjustment on the delivery method of teaching-learning. To be specific, the teaching-learning process is about how teacher and students interact each other based on a certain method of learning.Purpose: This study aims to investigate to what extent the NHT method can be used for an alternative method in promoting teaching-learning process in COVID-19 era.Design and methods: The study used library research method which investigates data from the documents, such as articles, news, books etc. related to NHT. The findings are validated by using triangulation data source technique.Results: the study reveals Transforming the method of teaching from offline class to online class is a way to solve in transferring the knowledge to the students. NHT is one of the many methods can use the meetings conference platform.